THE EFFECTIVENESS OF CHEMICAL MODULE WITH COMPENDIUM VERSES QURAN IN PESANTREN-BASED SCHOOL - Nurul - Hidayati; Sulistyo Saputro; Endang Susilowati (Jurnal Kependidikan, 2018)
This study was aimed at determining the effectiveness of chemical modules with compendium verses Quran to improving student learning outcomes in Pesantren-based school. The study used the research and development method with five stages: analysis, design, development, implementation, and evaluation. The data show that 99% of students and teachers need comparative science course modules with compendium from the Quran. The modules that have been produced are validated by material experts, linguists, learning experts, media experts, and practitioners. The results show that the module has been feasible to be implemented in classroom learning. The validation results show that the product is valid and feasible to use. The trial is limited and the main test is performed after module revision. The average pretest and posttest results show that with the use of the development module the results increase, so the use of this module is more effective because it improves students’ achievement. The significance value of the t-test is 0.001 which means there is an influence on the use of chemical modules with compendium verses from the QuranKEEFEKTIFAN MODUL KIMIA DENGAN KOMPENDIUM AYAT-AYAT ALQURAN PADA SEKOLAH BERBASIS PESANTRENAbstrakPenelitian ini bertujuan untuk menguji efektivitas modul kimia dengan dilengkapi kompendium ayat-ayat Alquran dalam meningkatkan hasil belajar siswa pada sekolah berbasis pesantren. Penelitian ini merupakan penelitian pengembangan dengan lima tahapan yaitu: analysis, design, development, implementation, dan evaluation. Data menunjukkan bahwa 100% siswa dan guru membutuhkan modul mata pelajaran kimia berkompendium Alquran. Modul yang telah dihasilkan divalidasi oleh ahli materi, ahli bahasa, ahli pembelajaran, ahli media, dan praktisi. Hasil menunjukkan bahwa modul layak diimplementasikan dalam pembelajaran di kelas. Hasil validasi menunjukkan bahwa produk tersebut valid dan layak untuk digunakan. Uji coba terbatas dan uji coba utama dilakukan setelah dilakukan revisi modul. Hasil rata-rata pretest dan posttest menunjukkan terjadinya peningkatan hasil dengan penggunaan modul pengembangan. Penggunaan modul ini lebih efektif karena meningkatkan prestasi siswa. Nilai signifikansi dari uji-t adalah 0,001. Artinya, terdapat pengaruh pada penggunaan modul kimia dengan kompendium ayat-ayat Alquran.